Laser-reduced graphene-oxide/ferrocene: a 3-D redox-active composite for supercapacitor electrodes. Issue 41 (12th October 2018) - Borenstein, Arie; Strauss, Volker; Kowal, Matthew D.; Yoonessi, Mitra; Muni, Mit; Anderson, Mackenzie; Kaner, Richard B.
Abstract : Supercapacitors are energy storage and conversion devices that display high power. Abstract : Supercapacitors are energy storage and conversion devices that display high power. In order to increase energy density, redox-active materials can be incorporated into the carbonaceous electrode(s). Although in recent years many studies have offered different redox-active candidates and composite methods, there is a constant search for an effective, easily producible and stable composite material. Here, we present a graphene/ferrocene composition as a redox active 3-D supercapacitor electrode material. The combination of highly reversible, conductive and strongly attached ferrocene with the high surface area and open porous structure of graphene results in high-power, high-energy density supercapacitors. The graphene scaffold is converted from graphene-oxide (GO) by laser irradiation, a facile, fast and eco-friendly method. The ferrocene is chemically bonded to the graphene by two different approaches that take advantage of the strong and stable pi–pi interactions between the carbon and the aromatic ligands. The excellent bonding between the components results in low internal resistance and high reversibility of the redox reaction. The composite demonstrated a 205% increase in specific capacitance from 87 F g −1 for pure laser reduced graphene oxide to 178 F g −1 for the composite with ferrocene. This is equivalent to an energy density of 6.19 W h kg −1 while maintaining a power density of 26.0 kW kg −1 .